The Influence of Lean Management on Worker Safety and Patient Safety Culture at Bhayangkara Brimob Kelapadua Hospital, Depok - Priyo Nugroho; Yanuar Jak; Apri Sunadi; Yenni Ariestanti (Journal of Ageing And Family, 2024)
In the modern era, hospitals are required to enhance worker safety and patient safety culture to provide optimal healthcare services. One approach used is Lean Management, which aims to reduce waste and improve efficiency in healthcare service processes. However, the implementation of Lean Management in hospitals still faces various challenges, particularly regarding its impact on worker safety and patient safety culture.This study aims to analyze the effect of Lean Management on worker safety and patient safety culture at Bhayangkara Brimob Kelapadua Depok Hospital. This research employs a quantitative method with an analytical survey design and a cross-sectional approach. Data were collected from healthcare workers in the inpatient unit using a validated and reliable questionnaire. Data analysis was conducted using linear regression to examine the relationships between variables. The results indicate that Lean Management has a positive and significant effect on worker safety (p = 0.000) and patient safety culture (p = 0.000). Additionally, worker safety acts as a mediator in the relationship between Lean Management and patient safety culture. These findings confirm that effective implementation of Lean Management can improve worker safety, which ultimately contributes to enhancing the patient safety culture. This study provides insights for hospital management on optimizing Lean Management implementation to create a safer work environment and improve healthcare service quality. It is recommended that hospitals strengthen training and safety policies to support more effective Lean Management implementation.